Assessment tax arrears at local authorities - Sazawati Salleh
Problem Statement: The problem of tax arrears has become a major issue In Local Authorities (PBTs). The performance of tax revenue collection is getting reduced and tax arrears are increasing at PBT. This issue is a serious problem and is very difficult to overcome. The problem arises from various factors such as the taxpayer's attitude, management and administration method of PBT. The low tax collection perfonnancc phenomenon has led the PBT to not carry out responsibilities to the population such as providing the best service. Approach: This study was conducted on the sample of Marang District Council in Terengganu which has 20 thousand taxpayers. Several interview sessions were conducted to 10 residents in Marang and interviews were made to 3 officers at Marang District Council. Survey findings: The findings show that tax arrears occur because of the taxpayers' attentive attitude that they are not obliged to pay taxes. Other factors that led to the increasing amount of tax arrears were due to the fact that the bill was not JJ1 the hands of the owner besides the taxpayer's financial problems. In conclusion: In addressing this tax arrears issue, the Local Authorities should take more aggressive action to collect these tax arrears. In addition, the Local Authorities need to create awareness and promotion campaigns to encourage taxpayers to make payments.